Sequence characteristics within nuclear genes from Sordaria macrospora - S. Pöggeler (Fungal Genetics Reports, 1997)
This paper reports sequence features within nuclear genes from Sordaria macrospora. Eight nuclear gene sequences were analyzed for codon usage, GC content, intron regulatory sequences and translation initiation sites.